2016
DOI: 10.17138/tgft(4)112-121
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the utilization of desho grass (Pennisetum pedicellatum) by farmers in Ethiopia

Abstract: A study was conducted to document how smallholder farmers in Ethiopia utilize desho grass (Pennisetum pedicellatum) and explain the determinants of alternative and competing uses of the grass. The study was conducted using a semistructured questionnaire for 240 farmers in the districts of Burie Zuria and Doyogena, complemented with input from key informants and secondary data. The dependent variables tested were the use of desho grass as a feed, multipurpose uses of the grass and types of livestock fed. To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
10
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 2 publications
12
10
3
Order By: Relevance
“…It is noted that training on livestock husbandry is essential to livestock owners to increase production and productivity of their stock. This finding agrees with earlier reports of Asmare et al [11] for cultivated forage production and management in selected areas of Ethiopia. It is noted by Ampaire and Rothschild [38] that training on livestock husbandry is essential to livestock owners to increase production and productivity of their stock.…”
Section: Training On Horse Husbandrysupporting
confidence: 93%
See 4 more Smart Citations
“…It is noted that training on livestock husbandry is essential to livestock owners to increase production and productivity of their stock. This finding agrees with earlier reports of Asmare et al [11] for cultivated forage production and management in selected areas of Ethiopia. It is noted by Ampaire and Rothschild [38] that training on livestock husbandry is essential to livestock owners to increase production and productivity of their stock.…”
Section: Training On Horse Husbandrysupporting
confidence: 93%
“…The age structure of household heads in both districts was similar in both sexes. The results of both districts were similar to the reports of Solomon et al [13]; Asmare et al [11] who reported the average age of respondents was 43.2 ± 1.0 years for Metekel Zone, north-western Ethiopia. The average family size of respondents in both districts in the present study was comparable with Asmare et al [11] but lower than districts (Mandura and Pawe) of Metekel zone of Benishangul-Gumuz region ranging 6.04-6.94 [14]; the reports by Tesfaye [15] with overall mean family size of 5.7 persons in Metemma district in Northwest Ethiopia and national average (5.20).…”
Section: Household Characteristicssupporting
confidence: 89%
See 3 more Smart Citations